Practice of relationships between the Prosecutor’s office and the gendarmerie in the investigation of political crimes - V. P. Gorbachov (Bulletin of Kharkiv National University of Internal Affairs)
The article discusses the practice of the relationships between the Prosecutor’s office and the gendarmerie, which formed during the investigation of political crimes in the Russian Empire after the judicial reform of 1864.